2016
DOI: 10.1145/3022671.2984001
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and thread-safe objects for dynamically-typed languages

Abstract: We are in the multi-core era. Dynamically-typed languages are in widespread use, but their support for multithreading still lags behind. One of the reasons is that the sophisticated techniques they use to efficiently represent their dynamic object models are often unsafe in multithreaded environments. This paper defines safety requirements for dynamic object models in multithreaded environments. Based on these requirements, a language-agnostic and thread-safe object model is designed that maintains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Wireless Communications and Mobile Computing managed programs is supported by approaches like Espresso [22]. Nowadays, C++ programs, as opposed to C programs, make extensive use of dynamic memory for short-term allocations, which often results in faster access to objects and thus increases program efficiency [23]. In comparison to C programs, studies have shown that C++ programs invoke dynamically created objects much faster and with fewer errors [24].…”
Section: Literature Surveymentioning
confidence: 99%
“…Wireless Communications and Mobile Computing managed programs is supported by approaches like Espresso [22]. Nowadays, C++ programs, as opposed to C programs, make extensive use of dynamic memory for short-term allocations, which often results in faster access to objects and thus increases program efficiency [23]. In comparison to C programs, studies have shown that C++ programs invoke dynamically created objects much faster and with fewer errors [24].…”
Section: Literature Surveymentioning
confidence: 99%